To Delegate or Not to Delegate: Gender Differences in Affective Associations and Behavioral Responses to Delegation - Akinola, Modupe; Martin, Ashley E.; Phillips, Katherine W. (Academy of Management journal, 2018)
Effectively delegating work to others is considered critical to managerial success, as it frees up managers’ time and develops subordinates’ skills. We propose that female leaders are less likely than male leaders to capitalize on these benefits of delegating. Although delegation has communal (e.g., relational) and agentic (e.g., assertive) properties, we argue that female leaders, as compared to male leaders, find it more difficult to delegate tasks due to gender-role incongruence. In five studies, we draw upon social role and backlash theories to show that women imbue delegation with more agentic traits, have more negative associations with delegating, and feel greater guilt about delegating than men. These associations result in women delegating less than men and, when they do delegate, having lower-quality interactions with subordinates. We further show that reframing delegation as communal attenuates women’s negative associations with delegation. These findings reveal that even when a given behavior has both agentic and communal elements, perceptions of agency can undermine women’s engagement in them. However, emphasizing the communal nature of seemingly agentic acts may encourage women’s engagement in such critical leadership behaviors. These findings have theoretical and practical implications for research on gender differences and leadership behavior in the workplace.